THE POTENTIAL OF RUBBER AGROFORESTRY FOR RATTAN (Calamus sp) CULTIVATION IN KATINGAN REGENCY: DIVERSITY OF CLIMBING TREES FOR RATTAN - Rotinsulu, Johanna Maria; Suprayogo, Didik; Guritno, Bambang; Hairiah, Kurniatun (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
This research aims to evaluate the diversity of climbing trees for rattan in agroforestry system. The result of this research is expected to be applied as the standard to improve the management in rattan agroforestry. The research was conducted from June to December 2011 in three different villages: Kalemei, Hiran and Liting in Katingan regency, Central Kalimantan. The data were collected via purposive sampling in two different types of land cover i.e rubber agroforestry (RA) and secondary forest (SF), each of system had 6 plots and 18 sub-plots of experiment. The evaluation of species diversity was performed by measuring species richness, Importance Value Index, and Diversity Index. Statistic model was constructed by employing the approach in multivariate analysis and cluster analysis. The results indicated that SF had higher species diversity (3.02 – 3.45). The diversity level of RA was higher in Hiran village (3.96), than in the other two villages (<3.0). Habitat similarity was characterised by the similar composition and structure of vegetation of both SF and RA in Hiran and Kalemei, but not in Liting. The potential of supporting trees for rattan in RA is rather high as shown by high species density and the presence of trees with high wood density (0.75-0.9g cm-3) to extremely high (>0.9g cm-3) as it found in SF.Keywords: Rattan, rubber agroforestry, climbing trees for rattan, secondary forest